2009
DOI: 10.5688/aj730228
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence the Career Goals of Pharmacy Students

Abstract: Objectives. To identify pharmacy students' short-and long-term career goals, including projected areas of practice, and evaluate the factors that influence these goals. Methods. A 19-question survey instrument was administered to pharmacy students in each of the 4 professional pharmacy years. The results were analyzed to determine factors influencing students' career goals and to compare choices among the different classes. Results. The most important factor considered by pharmacy students was work environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 4 publications
8
52
2
5
Order By: Relevance
“…More than half (50.9%) of respondents in the study by Savage et al chose retail pharmacy as their projected area of practice upon graduation, followed by independent pharmacy (18.6%) and clinical pharmacy (18.3%). 13 This study revealed that job preferences for hospital pharmacy ( p 5 0.001), pharmaceutical industry ( p 5 0.003), community pharmacy ( p 5 0.002), and academia ( p 5 0.026) were significantly different between students from public and private universities.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…More than half (50.9%) of respondents in the study by Savage et al chose retail pharmacy as their projected area of practice upon graduation, followed by independent pharmacy (18.6%) and clinical pharmacy (18.3%). 13 This study revealed that job preferences for hospital pharmacy ( p 5 0.001), pharmaceutical industry ( p 5 0.003), community pharmacy ( p 5 0.002), and academia ( p 5 0.026) were significantly different between students from public and private universities.…”
Section: Discussionmentioning
confidence: 97%
“…15 Savage et al reported that participants rated work environment (97.6%) as the most important factor for job consideration, followed by benefits (94.7%), flexible work schedule (92.9%), salary (84.9%), geographical location (78.1%), and advancement opportunities (66.6%). 13 Carter et al reported that most recently graduated pharmacists working in community and hospital pharmacies cited ''personally rewarding'' as the most important factor in deciding their career. 5 Respondents in our study were shown a list of common areas of practice most relevant to Malaysian pharmacists' roles and asked to rank, in descending order, their preferences of these areas of practice, assuming there was no 4-year mandatory service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies existing on pharmacists' career preferences focused on the type of practice (eg, community vs. institutional practice) rather than the type of location. 13,14 The extent to which research findings on recruitment and retention of physicians in rural practice also apply to pharmacists is unknown. Hence, this study was undertaken to examine the job location decision of new pharmacy graduates, and the workplace, community, familial, financial, and recreational factors influencing that decision.…”
Section: Introductionmentioning
confidence: 99%